Rahmat dan Sakramen: Teologi dengan Paradigma Kebebasan - Sunarko, Adrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
Theology with ‘freedom’ paradigm understands grace not as a third matter between God and humans. The nature of grace is God and God’s actions in relationship with and insofar as humans experience them. With regard to the attempts to understand the relation between grace and the sacraments, an integrated description of the sacrament as a representative and real symbol could be formulated. God is present in the sacraments through the particular symbols and when God is present, God is therefore realising humans’ salvation through the real symbols. In a sacramental celebration, with all the complexities of its forms and activities, the faithful experience how God is exceptionally present (in representative symbols) and when God is present salvation is realised or embodied (in real symbols). This is an explanation of how grace is conveyed through the celebration of the sacraments.